2018
DOI: 10.1038/s41419-017-0131-3
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-874 suppresses tumor proliferation and metastasis in hepatocellular carcinoma by targeting the DOR/EGFR/ERK pathway

Abstract: The δ opioid receptor (DOR) is involved in the regulation of malignant transformation and tumor progression of hepatocellular carcinoma (HCC). However, regulation of the DOR in HCC remains poorly defined. We found that miR-874 was identified as a negative regulator of the DOR, which is a direct and functional target of miR-874 via its 3′ untranslated region (UTR). Moreover, miR-874 was downregulated in HCC and its expression was inversely correlated with DOR expression. Downregulation of miR-874 was also assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…In this research, we analysed miR-874 expression in both RB tissues and cell lines. The data of RT-qPCR analysis indicated that miR-874 (23,24). miR-874 expression is also downregulated in osteosarcoma tissues and cell lines (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…In this research, we analysed miR-874 expression in both RB tissues and cell lines. The data of RT-qPCR analysis indicated that miR-874 (23,24). miR-874 expression is also downregulated in osteosarcoma tissues and cell lines (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…17 miR-874 represses HCC progression via modulating the δ opioid receptor (DOR). 18 Currently, we reported LINC00152 was overexpressed in HCC cells whereas miR-215 was inhibited. CDK13 was speculated as the putative target of miR-215.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, miR‐138 can inhibit HCC via modulating SP1 . miR‐874 represses HCC progression via modulating the δ opioid receptor (DOR) …”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are noncoding endogenous RNA molecules with a length of 18~25 nucleotides, which are partially or completely complementary to the 3 ′ or 5 ′ untranslated region (UTR) of target genes [1,2]. miRNAs play a vital role in a wide range of biological processes including cell proliferation, differentiation, and apoptosis [3][4][5][6][7]. In addition, increasing evidences have been revealed demonstrating that the occurrences of many diseases including cancers are closely associated with abnormal expression of specific miRNAs [8], e.g., prostate cancer-associated miR-21 and miR-141 [9], breast cancer-associated miR-155-3p [10], and liver fibrosis-associated miR-378 [11].…”
Section: Introductionmentioning
confidence: 99%